A Study on Energy Import Dependency in India (International Journal of Innovative Research in Engineering & Management, 2024)
In today's globalized world, the  interconnection between the economy and the environment  is evident. A nation's prosperity and self-reliance hinge on  adopting sustainable methods of energy production. Lack of  energy security and self-sufficiency compels a country to  import necessary energy resources, significantly impacting  both sustainability and the foreign reserves. This paper  addresses India's suboptimal utilization of energy resources,  focusing on the import dependency in the energy sector due  to the prevalent use of fossil fuel-based energy  (conventional energy) from 2006 to 2020. Data analysis,  incorporating graphical representations of conventional  energy import and consumption, highlights the status,  growth, and import dependency trends. The findings reveal  that India heavily relies on imports for conventional energy  resources, particularly crude oil. The paper concludes that  the key solution for improving economic and environmental  conditions lies in transitioning towards renewable energy  resources.
Keywords: Energy Import Dependency; Conventional Energy Consumption; Sustainability; Renewable Energy